Discovery and Optimization of Dibenzodiazepinones as Allosteric Mutant-Selective EGFR Inhibitors - De Clercq, Dries J. H. (ACS Med Chem Lett, 2019)
[Image: see text] Allosteric kinase inhibitors represent a promising new therapeutic strategy for targeting kinases harboring oncogenic driver mutations in cancers. Here, we report the discovery, optimization, and structural characterization of allosteric mutant-selective EGFR inhibitors comprising a 5,10-dihydro-11H-dibenzo[b,e][1,4]diazepin-11-one scaffold. Our structure-based medicinal chemistry effort yielded an inhibitor (3) of the EGFR(L858R/T790M) and EGFR(L858R/T790M/C797S) mutants with an IC(50) of ∼10 nM and high selectivity, as assessed by kinome profiling. Further efforts to develop allosteric dibenzodiazepinone inhibitors may serve as the basis for new therapeutic options for targeting drug-resistant EGFR mutations.